(3LGeY GdCUhd dCMGOjK GdQShds - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s
(3ChdgG (B:s
(3GdcJGH GdKGfi ef MQa GdaGA ai GdaQGFV hGdehGQjK , hajg KdGKI aUhd s
(3BNQgG (B:s
(3BNQg ef TQM ZQjH GdcGa (B" (3bhdg (B: (3fcJI (B: (3GdfcJI GdCKQ ai GdTF fLR RHQ gPG GdcJGH GdeHGQc , hGdMeO ddg s
(3GdLRA GdSGHY ef fSNI CNQis
(3HMhGTjgG ebGHdGJs
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3GdfSNI HgG MhGT s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B272 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B174s
Keywords: (3GdMOjK h GdeUWdMs